Psychological Engagement of Students Enrolled in Schools through ‘Age-Appropriate-Grade’ Provision of RTE Act 2009: A Case of Deprived Urban Children in Uttarakhand - Chakraborty, Sushmita (INDIAN EDUCATIONAL REVIEW, 2016)
RTE Act 2009 has stated that children above six years who could not complete elementary education shall be admitted in ‘class appropriate to his or her age.’ To ensure that all such children complete elementary education it is necessary to ensure they become intrinsically motivated and feel engaged with their school and with learning, besides making systemic provision of access and bridging the learning gap. The sample of the present study included such students from Class III – VIII of government schools (urban and semi-urban areas) of two districts in Uttarakhand. Results throw light on perception of students towards their schools, teachers, peers as well as themselves, their psychological needs, factors which facilitate and factors which impede their psychological engagement with school. Understanding of the above may help schools to create a conducive environment for active involvement of these students with school activities and thus facilitate their completion of elementary education.